2021
DOI: 10.1186/s12884-021-03838-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Arabin pessary in women at high risk for preterm birth: long-term experience at a single tertiary center in Malaysia

Abstract: Background Spontaneous preterm birth is a global issue that contributed to perinatal morbidities and mortalities worldwide. The study aimed to describe the experience at UKM Medical Center in managing women at high risk for spontaneous preterm birth using the Arabin pessary. Methods This is a retrospective observational study involving 58 pregnancies from 1st January 2013 to 31st December 2019. Inclusion criteria were previous mid-trimester miscarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Specifically, prematurity was 14% in the vaginal pessary group versus 29% in the monitoring group (RR 0.49, 95% CI 0.24, 0.97), while poor perinatal outcome was 2% in the vaginal pessary group versus 29% in the monitoring group (RR 0.4, 95% CI 0.19, 0.83). The results were even more encouraging in the subanalysis of high-risk pregnancies for the occurrence of preterm birth [42][43][44][45][46][47][48][49][50].…”
Section: Vaginal Pessarymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, prematurity was 14% in the vaginal pessary group versus 29% in the monitoring group (RR 0.49, 95% CI 0.24, 0.97), while poor perinatal outcome was 2% in the vaginal pessary group versus 29% in the monitoring group (RR 0.4, 95% CI 0.19, 0.83). The results were even more encouraging in the subanalysis of high-risk pregnancies for the occurrence of preterm birth [42][43][44][45][46][47][48][49][50].…”
Section: Vaginal Pessarymentioning
confidence: 99%
“…In addition, there was no difference in the reduction of preterm birth before 37 weeks gestation when the combined treatment of cervical banding and progesterone administration was compared with cervical banding alone (RR 1.04, 95% CI 0.56, 1.93) or progesterone administration. (RR 0.82, 95% CI 0.57, 1.19) [48,[51][52][53][54].…”
Section: Combination Of Therapeutic Approachesmentioning
confidence: 99%
“…Early screening, identification, and prevention in asymptomatic pregnant women with risk factors for preterm birth can help reduce the incidence and mortality of preterm births. Many studies have shown that implementing adequate programs to prevent preterm birth is desirable [ [9] , [10] , [11] , [12] ]. This prediction model is a promising approach for identifying risk factors and estimating the probability of preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction models for preterm birth are a promising approach to realize risk estimation and the implementation of adequate programs for preventing preterm birth is desirable. Studies show that progesterone and pessary insertion are beneficial to prevent preterm birth in women who are at high risk for preterm birth 18–21 . However, there is limited evidence on the reporting quality and risk of bias of prediction models using machine learning methods in preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that progesterone and pessary insertion are beneficial to prevent preterm birth in women who are at high risk for preterm birth. 18 , 19 , 20 , 21 However, there is limited evidence on the reporting quality and risk of bias of prediction models using machine learning methods in preterm birth. Therefore, we conducted a systematic review to assess the reporting quality and risk of bias of studies on machine learning‐based prediction models in preterm birth.…”
Section: Introductionmentioning
confidence: 99%